2014
DOI: 10.1016/j.ultrasmedbio.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Normal and Infarcted Myocardium Measured by a Multifrequency Shear Wave Method: Comparison with Pressure-Segment Length Method

Abstract: Our aims were (i) to compare in vivo measurements of myocardial elasticity by shear wave dispersion ultrasound vibrometry (SDUV) with those by the conventional pressure-segment length method, and (ii) to quantify changes in myocardial viscoelasticity during systole and diastole after reperfused acute myocardial infarction. The shear elastic modulus (μ1) and viscous coefficient (μ2) of left ventricular myocardium were measured by SDUV in 10 pigs. Young’s elastic modulus was independently measured by the pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 45 publications
6
70
0
Order By: Relevance
“…As was indicated previously, a number of studies have been performed to measure the potential of using SWEI measurements for systolic and diastolic functional assessment . Pernot et al reported a linear relationship between the maximum shear stiffness measurement and the intra‐ventricular pressure in systole after using an inotropic agent; the results reported here are consistent with those results .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As was indicated previously, a number of studies have been performed to measure the potential of using SWEI measurements for systolic and diastolic functional assessment . Pernot et al reported a linear relationship between the maximum shear stiffness measurement and the intra‐ventricular pressure in systole after using an inotropic agent; the results reported here are consistent with those results .…”
Section: Discussionsupporting
confidence: 90%
“…We have previously investigated the potential of SWEI to provide contractility, compliance, and relaxation time constant measurements for cardiac function assessment . There are a number of publications regarding cardiac functional assessment using this method, and further details are included in the discussion section . However, the relationship between the intraventricular pressure and SWEI or ARFI measurements during the cardiac cycle has not been studied.…”
mentioning
confidence: 99%
“…Other techniques are now under development to estimate myocardial shear elasticity/viscoelasticity [2, 5, 13, 19, 29, 38, 42, 43]; however, transthoracic measurements are still technically challenging and require special equipment or are based on magnetic resonance imaging, which has limited availability. Conversely, TDI is now available on all commercial systems for cardiac imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[12]–[14]), to the best of our knowledge, there is no published research that has described relaxation time constant measurements of the heart using ARFI and SWEI. In this paper, we investigate the relationship between ARFI and SWEI measures of the relaxation time constant and the systolic/diastolic stiffness ratio.…”
Section: Introductionmentioning
confidence: 99%